Electrocardiographic imaging a valid tool or an inaccurate toy?. (19th May 2022) - Parreira, A; Carmo, P; Mesquita, D; Marques, L; Chambel, D; Pinho, J; Ferreira, A; Amador, P; Chmelevsky, M; Machado, P; Ferreira, J; Nunes, S; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private hospital(s). Main funding source(s): Learning Health Background and aim: Electrocardiographic imaging (ECGI) is capable of performing an activation map with a single beat. However, previous studies using the epicardial-only system, have suggested a bad accuracy for the assessment of the epicardial breakthrough. Recent systems using endo-epicardial analysis have shown promising results. The aim of this study was to assess the accuracy and reproducibility of two endo-epicardial ECGI systems using different cardiac sources one based on the extracellular-potential, and the other on the equivalent double layer model, respectively the AMYCARD (EP Solutions SA, Switzerland) and VIVO (Catheter Precision, NJ USA) systems. Methods: We studied 11 consecutive patients referred for ablation of frequent idiopathic premature ventricular contractions at our center that had an ECGI performed using both systems on the same day. The AMYCARD system uses a dense array of body-surface electrocardiograms with up to 224 leads and VIVO uses just the 12-leads ECG. Both systems use a patient-specific heart torso geometry obtained with a CT-scan or cardiac magnetic resonance. The localisation of the PVCs based on ECGI was done using a segmental model with 22 segments on the left ventricle, to include the classical 17 segment model plus the aortic cusps and the papillary muscles, and 12 segments on the right ventricle including 4 on the right ventricular outflow tract (RVOT): (anterior, lateral, right septum and left septum). A perfect match was defined as a predicted location within the same anatomic segment, whereas a near match as a predicted location within the same segment or a contiguous one. Results: The median (Q1-Q3) number of leads used for the AMYCARD was 131 (118-144). Seven patients underwent ablation and in 4 ablation is pending. The predicted locations and the ablation site are depicted on the Table. We found a perfect match between both systems in 73% (Figure) and near match in 91% of cases. In patients that underwent ablation the systems localised the site of origin of the PVCs within the same segment or the contiguous segment in all patients with VIVO and in six out of seven with AMYCARD. Conclusions: ECGI is an accurate diagnostic tool with reproducible results regardless the cardiac source used for analysis.